Konsep Pendidikan Berbasis Gender dan Relevansinya dengan Tujuan Pendidikan Islam: (Studi Analisa Pemikiran R.A. Kartini) - Rosyida, Nailur; Rohmah, Nafilatur (PSGA Institut Agama Islam Tarbiyatut Tholabah, 2023)
Gender based education is education that aims to provide justice and harmony for men and women. Gender based education is based on the inequality beetwen men and women. R.A. Kartini is one of the figures who initiade gender based education wich contains equality education and character education. Equalityeducation teaches how students as human beings have the same rights and obligations, not differentiated on the basis of gender and socio-economic background. While character education teaches how important morals are to balance the intellegience of the brain. The study aims to determine the concept of gender based education and its relevance to the goals of Islamic education. By using this type of library reseach, this research requires quite a lot of documents such as book, articles, journals and other documents. The data sources of this reseach were obtained from primary data (basic data) and secondary data (supporting or supporting data). The analytical method used in this research is qualitative anlysis. From the results of this study it is known that gender based education R.A. Kartinihas a similiar pattern of ideas with the purpose of Islamic education in particular, namely education is required for men and women by providing (science) as wellas forming morals so that later men and women work together to advance the nation.